Acid Lactic Bacteria as a Bio-Preservant for Grape Pomace Beverage - Dias, Juliana Furtado; Simbras, Beatriz Duarte; Beres, Carolina; dos Santos, Karina Olbrich; Cabral, Lourdes Maria Correa; Miguel, Marco Antônio Lemos (Frontiers in Sustainable Food Systems, 2018)
Probiotized juice represents an alternative to probiotic beverages derived from dairy products. Agricultural residue production represents an economical and environmental problem worldwide, its utilization to supplement a probiotic juice may be an applicable solution on food industry. Studies using fruit residues as an ingredient are not a novelty; however a definitive solution to this environmental problem has not yet been established. Therefore, the objective of this work was to propose a probiotized juice using lactic bacteria that, besides being a starter culture, can function as biopreservative and improve the stability of the final product. A fermented beverage was formulated using commercial grape juice, Vitis vinifera Pinot noir grape pomace and lactic bacteria. Pathogenic strains were used to simulate a potential protective effect on the beverage. Procedures were carried out according to the American Public Health Association and the results were expressed in media with standard deviation using statistical analyses performed by Prism. Lactic bacteria showed a cell growth of approximately 4 log CFU/ml. There was a significant decrease in pH values (p < 0.05) when pure grape juice was fermented. Grape juice supplemented with grape pomace from white winemaking was able to induce a higher growth of lactic bacteria population during fermentation, 5 log cycle CFU/mL, comparing to juice without supplementation. The beverage containing grape juice, water and pomace also presented growth on lactic bacteria population but Lactobacillus rhamnosus reached a higher concentration, of approximately 8 log cycle CFU/ml after 12 h fermentation. This was also observed when beverages were stored, only L. rhamnosus remained viable for 10 days at 10°C. All beverage samples co-inoculated with food borne pathogens, presented a stable and higher lactic bacteria population (2 log CFU/g) when compared to the added pathogen population. The final probiotic strain cells was above 8 log cycle CFU/mL, L. rhamnosus wasn't able to reduce significantly pathogenic population, however a bacteriostatic effect was observed. The probiotic beverage obtained represents a promising application for grape pomace. More studies are needed to investigate the causes and interactions of grape pomace compounds and lactic acid bacteria against food borne pathogens.